The impact of using e-learning on the student's performance in 3rd developing countries: a pilot study - Al-yousef, Ali; Aljaraideh, Yousef; Obiedat, Mamoon; Barakat, Eyad; Habboush, Ahmad (International Journal of Engineering and Technology, 2019)
E-learning is one of the growing areas especially in the higher education. There are several advantages for using e-leaning in the student performance. In third developing countries such as Jordan, important steps were taken for adopting the e-learning system. This is done by providing students with technological and communicational skills as well as to making students more adaptive to the technology of contemporary societies. Several studies have been analysis the effect of the e-learning on the student performance and found that there is a tangible enhancement on the student performance and is considered as key element that positively affect the student motivations. Online courses at Jerash university like; computer skills accessed by students through electronic gate (Moodle).This study used SPSS to analysis the performance of 63 student (32 e-learning and 31 traditional learning).the study found that there are statistically significant differences between the two group in favor of experimental group.Â Â